2020
DOI: 10.1186/s12889-020-09208-0
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in demographic, social and health-related factors associated with loneliness across the adult life span (19–65 years): a cross-sectional study in the Netherlands

Abstract: Background: Recognition of loneliness as a health concern among adults stresses the need to understand the factors associated with loneliness. Research into factors of influence in the various phases of the adult life span (19-65 years) is scarce. Therefore, the associations between demographic, social and health-related factors and loneliness among young (19-34 years), early middle-aged (35-49 years) and late middle-aged adults (50-65 years) were explored. Methods: A secondary analysis with a large cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 63 publications
5
90
1
1
Order By: Relevance
“…Loneliness is “the unpleasant experience that occurs when a person’s network of social relations is deficient in some important way, either quantitatively or qualitatively” [ 48 ]. Accordingly, in non-pandemic era, commonly reported factors associated with loneliness are marital status of “unmarried”, living alone, social exclusion, less frequent contact with neighbors, and poor family and non-family relationships [ 22 , 49 , 50 ]. However, in the present study, epidemic-related factors such as having SARS-CoV-2-infected acquaintances were associated with loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness is “the unpleasant experience that occurs when a person’s network of social relations is deficient in some important way, either quantitatively or qualitatively” [ 48 ]. Accordingly, in non-pandemic era, commonly reported factors associated with loneliness are marital status of “unmarried”, living alone, social exclusion, less frequent contact with neighbors, and poor family and non-family relationships [ 22 , 49 , 50 ]. However, in the present study, epidemic-related factors such as having SARS-CoV-2-infected acquaintances were associated with loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study, which used data from the large, global BBC Loneliness Experiment, however, showed that loneliness was greater in men than women, particularly younger men living in individualistic cultures ( Barreto et al, 2021 ). Furthermore, the relationship between being ethnically different from the mainstream culture and loneliness has been explored and is strongest among young and early middle-aged adults (19–34 and 35–49 years old) compared to other age groups ( Franssen et al, 2020 ). In another study, young British adults (16–24 years old) who identified as black or an ethnic minority were more likely to report higher levels of loneliness than those who did not ( Office for National Statistics, 2018a ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that loneliness and social isolation are related to each other but should be distinguished [ 11 , 12 ]. Both concepts may have independent effects on health and, therefore, should be regarded as individual factors, even though both have been associated with a decline in health status and quality of life [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Associations between loneliness, and individual factors (e.g., behavior) and community factors (e.g., attitude, relationship between community members) have not yet been explored among mothers with young children. Recent studies on loneliness in the general population have reported associations of loneliness with individual variables; health-related behavioral variables [ 3 , 22 , 23 ]; community variables, such as trust in community neighborhood [ 22 ], and frequency of neighbor contact among adults [ 11 ]; and social capital [ 24 ].…”
Section: Introductionmentioning
confidence: 99%